Antioxidant Functions of Nitric Oxide Synthase in a Methicillin Sensitive Staphylococcus aureus - Manisha Vaish; Vineet K. Singh (International Journal of Microbiology)
Nitric oxide and its derivative peroxynitrites are generated by host defense system to control bacterial infection. However certain Gram positive bacteria including Staphylococcus aureus possess a gene encoding nitric oxide synthase (SaNOS) in their chromosome. In this study it was determined that under normal growth conditions, expression of SaNOS was highest during early exponential phase of the bacterial growth. In oxidative stress studies, deletion of SaNOS led to increased susceptibility of the mutant cells compared to wild-type S. aureus. While inhibition of SaNOS activity by the addition of L-NAME increased sensitivity of the wild-type S. aureus to oxidative stress, the addition of a nitric oxide donor, sodium nitroprusside, restored oxidative stress tolerance of the SaNOS mutant. The SaNOS mutant also showed reduced survival after phagocytosis by PMN cells with respect to wild-type S. aureus.